PENGARUH ULASAN DAN PENILAIAN PELANGGAN, KUALITAS LAYANAN, DAN HARGA TERHADAP MINAT BELI KONSUMEN PADA PASAR ONLINE SHOPEE PADA MAHASISWA DI KOTA PONTIANAK - Ari Widiati AW (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
"The Influence of Customer Reviews and Ratings, Service Quality, and Prices on Consumer Buying Interest in the Shopee Online Market for Students in Pontianak City. Shopee is an e-commerce (web based buying and selling) in light of portable applications, which is right now creating in Indonesia, shopee offers fun, free and confided in web based trading through cell phones. With the shopee application, you can enlist selling items and shop for different appealing proposals at the most minimal costs and free delivery all through Indonesia. Shopee is an internet trading office that gives an assortment of items to help our every day exercises which incorporate style, devices, restorative devices, electronic gadgets, leisure activities and assortments, photography, athletic gear, auto, nutrients and enhancements, home apparatuses, food and drinks, trinkets and gatherings, to vouchers. This study aims to determine customer reviews and ratings, service quality, and prices on consumer buying interest in the online shopee market. This research is a survey research. The population used in this study were students in the city of Pontianak. The sample used was 100 respondents who were carried out with non-probability techniques. The method used is the associative method with a quantitative approach. The instrument validity test used Confirmatory Factor Analysis (CFA) and the reliability test used Cronbach's alpha. The analysis used is multiple regression path analysis, hypothesis testing using the coefficient of model accuracy or determination (R^2) partial testing (t test) and simultaneous (f). The data in this research are primary data taken using a questionnaire. Data testing was carried out with the help of the SPSS 16 program. The results of this study found that: 1) client audits and assessment factors didn't have a huge fractional impact on purchasing revenue in the shopee online market, (2) administration quality factors didn't significantly affect purchasing revenue in the shopee online market, (3) the value variable significantly affects purchasing revenue in the shopee online market.